KEDUDUKAN AHLI WARIS PADA PERKAWINAN POLIGAMI - Bambang Sugianto (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The marriage of polygamy is a marriage bond to which one of the parties to which a man has / marries several opposite sexes at the same time. And the marriage of a child in this marriage is legally so long as this marriage is recorded and performed in accordance with the legitimate requirements of marriage. In the division the inheritance of a child born of a polygamous marriage is determined the origin of the property whether the property left by the parent is a congenital treasure or a gifted property of the marriage.In article 94 paragraph (1) of Law number 1 year 1974 concerning marriage in which the implementation of inheritance in marriage can be done by agreement between all parties of heir. This will give many benefits to all heirs. If no agreement is reached then the division of inheritance in polygamous marriages can be done by filing a lawsuit inheritance in the Court. The obstacles in the division of inheritance in polygamous marriage is due to the unrecorded marriage in polygamous marriage, and polygamous marriage never entered into a marriage agreement and deliberated for division Inheritance often occurs due to obstacles or caused frequent unfairness in polygamous marriage.